STRATEGI FUNDRAISING WAKAF TUNAI PADA MI MA’ARIF AL FALAH JOYOKUSUMO BANJARNEGARA - Uut SetiyaMingrum; Dewi Laela Hilyatin (CV. KAMPUS AKADEMIK PUBLISING, 2024)
One of the instruments in Islam that is closely related to the people's economy is waqf. As time progresses, waqf is not only in the form of land and immovable objects, but there are also movable objects such as cash waqf. The potential for cash waqf in Indonesia is very large considering that the majority of the population adheres to Islam. However, in reality, many philanthropic institutions and waqf managers are not optimal in carrying out waqf fund collection activities. In fact, fundraising activities are the most important thing in an institution as a means of achieving institutional goals. Therefore, fund raising strategies are needed that must be developed by waqf nadzir. This research uses a type of field survey research with a qualitative approach. In data collection techniques, the author uses observation, interviews and documentation. Meanwhile, in data analysis techniques, the author uses data reduction, data presentation, and drawing conclusions or data verification. And in data validity techniques, the author uses triangulation of sources, techniques and time. This research was conducted at MI Ma'arif Al Falah Joyokusumo Banjarnegara which also carries out cash waqf fundraising activities for the development of madrasa facilities and infrastructure. The fundraising strategy implemented by MI Ma'arif Al Falah Joyokusumo Banjarnegara refers to the theory put forward by Holloway which divides three business categories in fundraising. First, collect funds from sources that are already available in the community, such as direct mail/proposals, family and alumni networks, pick-up and media campaigns, etc. Second, making waqf assets productive/creating new funds, such as building dormitory facilities. Third, collecting waqf funds by empowering waqf proceeds for the general public/mauquf'alaih, such as holding calligraphy and tilawati training for madrasa teachers. The research results show that MI Ma'arif Al Falah Joyokusumo Banjarnegara has succeeded in carrying out cash waqf fundraising activities in a short time, but achieved maximum collection results.